Coupled and coordinated development of water-energy-food-ecology-land system in the Yangtze River Delta, China - Qing Qin; Weijun He; Liang Yuan; Dagmawi Mulugeta Degefu; Thomas Stephen Ramsey (npj Clean Water)
Abstract The Yangtze River Delta (YRD) region, a pivotal economic hub in China, relies on water, energy, food, ecology, land, for its prosperity development. Therefore, evaluating their coupling and coordination aids the YRD’s sustainable development. This study integrated ecology and land into the water-energy-food system to form a water-energy-food-ecology-land system (WEFEFS), and the entropy weight model, comprehensive evaluation index model and coupling coordination degree models were used to assess the WEFELS in the YRD (2005-2022), and identified key influencing factors through an obstacle model. The results demonstrate that the comprehensive evaluation index of WEFELS in the YRD rose slowly, with the food system contributing the most (22.15%) and the water system contributed the least (18.25%). The degree of coupling coordination (DCC) of WEFELS in the YRD improved from 0.561 to 0.653, exhibiting spatiotemporal heterogeneity, with Anhui Province leading spatially. The main obstacle factors were Per land GDP and Energy self-sufficiency rate.